SHM_120459_HST_3D Vendel XII Helmet - Lernestål, Erik; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of the Vendel XII helmet, an iron helmet with bronze fittings. The helmet was excavated from an Iron Age boat grave (Vendel XII) in Vendel Parish, Uppsala County and is currently held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=849

Link to Sök I Samlingarna

https://samlingar.shm.se/object/8878740C-0E43-420A-9A94-BC793C0677D2
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; Dynamic Collections; 3D Model; Museum Object; Vendel; Swedish Iron Age; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi